2013
DOI: 10.1002/psp.1774
|View full text |Cite
|
Sign up to set email alerts
|

Euromarriages in Spain: Recent Trends and Patterns in the Context of European Integration

Abstract: This article examines recent trends and patterns in binational marriages between European citizens in Spain over a 20‐year period and the sociodemographic profile and nationality composition of these binational marriages. The analysis relies on aggregate marriage statistics and on marriage register microdata for 2008–2009. We use odds ratios to monitor trends and characteristics of binational marriages and multinomial regression to further examine the sociodemographic profile of these couples. The analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…By contrast, for both men and women higher education is mostly positively associated with the likelihood of marrying a partner from Western Europe or North America. Medrano et al (2014) find something similar when examining marriages between Spaniards and other Europeans, making a rough distinction between the natives of EU-15 countries and other EU countries (here labelled "new Europeans"): while a higher education level implies a higher likelihood of marriage with an EU-15 spouse, it is lower-educated Spaniards who have a tendency to marry immigrants from new EU member countries.…”
Section: Sánchezmentioning
confidence: 96%
“…By contrast, for both men and women higher education is mostly positively associated with the likelihood of marrying a partner from Western Europe or North America. Medrano et al (2014) find something similar when examining marriages between Spaniards and other Europeans, making a rough distinction between the natives of EU-15 countries and other EU countries (here labelled "new Europeans"): while a higher education level implies a higher likelihood of marriage with an EU-15 spouse, it is lower-educated Spaniards who have a tendency to marry immigrants from new EU member countries.…”
Section: Sánchezmentioning
confidence: 96%
“…Some quantitative studies (e.g. Glowsky 2011;González-Ferrer et al 2018;Medrano et al 2014;Schroedter/Rössel 2014;van Wissen/Heering 2014) have shown that exogamy is often accompanied by heterogamy in other traits, such as age, education, and cultural characteristics, and have traced this pattern back to status exchange mechanisms. Others see exogamy as having little connection to heterogamy in other characteristics, and explain intermarriage with a migrant using homogamy/preference theories (Çelikaksoy/Nielsen/Verner 2006).…”
Section: Mate Selection and Exogamy From The Natives' Perspectivementioning
confidence: 99%
“…While immigration is a relatively new issue in Eastern European countries (Salt 2011), in Western Europe different migrant generations and contexts coexist. In former colonial powers, natives may have more similarities to migrants from former colonies, due to a shared religion, and might have more differences to Eastern European migrants (Medrano et al 2014). In the older member states of the European Union, growing diversity stems largely from the immigration of Muslims (Modood 2003;van der Noll 2014).…”
Section: Mate Selection and Exogamy From The Natives' Perspectivementioning
confidence: 99%
“…Particularly studies into intra-European love migration and its effects on the individual level only recently emerged (Braun & Recchi, 2008;Díez Medrano, Cortina, Safranoff, & Castro-Martín, 2014;Gaspar 2008Gaspar , 2012Koelet, de Valk, & Willaert, 2011).…”
Section: Introductionmentioning
confidence: 99%